On Entire Functions Belonging to a Generalized Class of Convergence - Gal', Yu. M.; Mulyava, O. M.; Sheremeta, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
In terms of Taylor coefficients and distribution of zeros, we describe the class of entire functions f defined by the convergence of the integral \(_r_0 ^∞ γ (M_f (r)) r^ρ + 1 dr\) , where γ is a slowly increasing function.